Politics and power in early medieval Europe : Alsace and the Frankish Realm, 600-1000 - Hummer, Hans J. (Cambridge University Press, 2005)
Taking Alsace as its focus, this innovative study offers a unique snapshot of localised and centralised political structures in early medieval Europe. Providing a comprehensive exploration of the regional sources, it tracks the development and eventual demise of a distinctive political culture derived from networks of monasteries and kin-groups.
Keywords: Alsace (France) -- History.; Alsace (France) -- Politics and government.; Europe -- Politics and government -- 476-1492.; Alsace (France) -- Histoire.; Alsace (France) -- Politique et gouvernement.; Europe -- Politique et gouvernement -- 476-1492.; HISTORY.; Politics and government; Europe; France -- Alsace; Macht; Zentralgewalt; Mittelalter; Elsass; Fränkisches Reich; Frankische rijk.; Politieke macht.; 476-1492; History